Research on Making Orthophotos of Mountainous Areas Based on WorldView-2 Images - Xing, Zhu Rong; Feng, You Gui; Xie, Ji Ying; Wang, Lei; Xu, Yan Ming; Wei, Yequn (Journal of physics. Conference series, 2021)
Combining the RPC rational polynomial coefficient model, using WorldView-2 remote sensing images, combined with field surveyed control points, survey area digital elevation model DEM and other data to produce the mountain orthophoto map, combined with the detection points to analyze the accuracy of the results, solve the problem Topographic maps are difficult to measure and are subject to flight restrictions.